To Link or Not to Link: Clause Chaining in Japanese Narratives - Clancy, Patricia M. (Frontiers in Psychology, 2020)
Japanese is a clause-chaining language, in which a sentence is formed by linking two or more clauses in a series (chain), using different forms of the verb in “medial” clauses within the chain from the “final” clauses that end the chain. Since the verb comes at the end of a clause in Japanese, speakers must decide by the time they reach the verb at end of one clause whether or not to connect it to the following clause. This study analyzes the narratives of Japanese children and adults with the dual goal of discovering why narrators decide either to link the clause they are producing to the following clause or not to link, i.e., to end the clause chain. For this purpose, stories were elicited from 60 three- to seven-year old children and ten adults, who performed two tasks: 1) telling the story depicted in a hand-drawn cartoon, and 2) viewing a seven-minute video and then recounting the plot from memory. The data were analyzed qualitatively and quantitatively. The qualitative analysis examines story length and prompting, length of clause chains, variety of linking connectives, semantic relations—such as simultaneity, temporal sequence, and causality—between clauses in chains, shifts of subject from one story character to another (switch reference), and contexts in stories where narrators end clause chains. For the quantitative analysis, a multifactorial, mixed-effects model was fit to determine which of several potential predictors have a significant effect on the probability that narrators will link clauses. The model is significant, though weak in discriminatory power. The strongest effects are: 1) simultaneous relations between events increase the probability that narrators will link clauses, and 2) reaching the end of a narrative unit, e.g., an episode, increases the probability that narrators will end their clause chain. There are no significant age effects: the children respond in the same way to the predictors as the adults. The qualitative and quantitative results of the study are interpreted with respect to the close relation between grammar (clause chains) and discourse (narrative structure) as well as the cognitive process of producing clause chains during narration.